Challenges to transferring and sharing of tacit knowledge within a construction supply chain. Issue 1 (5th March 2019) - Saini, Mandeep; Arif, Mohammed; Kulonda, Dennis J.
Abstract : Purpose: This paper aims to investigate the potential challenges that hinder the effective transfer and sharing of tacit knowledge (knowledge communication [KC]) within a construction supply chain (CSC). Design/methodology/approach: This study identifies six challenges (through literature review) with 15 positive correlations between them. Quantitative methodology is used to validate those challenges and correlations between challenges. First, data are collected through semi-structured e-survey questionnaire. Afterwards, a Frequency and Kruskal–Wallis H test is run for initial validation of identified challenges. A correlation analysis is used to highlight the taxonomic relations between those challenges. Finally, the study establishes the rank order of the first and following challenges. Findings: This study highlights that traditional ways of working with construction organisations are the predominant challenge that hinders effective transferring and sharing of tacit knowledge. The cause of challenges is the fragmented nature of CSC. Also, it brings out the correlation between those challenges. The study draws the conclusion and recommendation to implement KC within a CSC. Originality/value: The study highlights the challenges that hinder KC in a construction process of a CSC. It establishes that the fragmented nature of the construction sector is not the first challenge that hinders implementation of transferring and sharing of tacit knowledge but somewhat traditional organisation structures and working processes. This is the first paper that investigates and tests the challenges in four dimensions and establishes the rank order of challenges with crucial distinction in a KC approach within a CSC.